Reliability and safety assessment of distribution networks in mountainous plateau areas subject to low-amplitude lightning - Tang, Yutao; He, Kai; Shu, Hongchun; Wang, Ke; Lou, Weijie; Qin, Zhong; Han, Yiming; Dai, Yue (Reliability engineering & system safety, 2025)
•The risks of LaL to distribution systems are assessed via data and modelling for the first time.•Using the HPLLS, the characteristics and patterns of LaL were detected and studied.•An FSM model was proposed to assessment and simulate the development patterns of LaL.•A risk assessment model for LaL overvoltage in distribution systems has been proposed. Lightning poses a primary threat to the safety and reliability of power systems, especially distribution networks are susceptible to lightning-related accidents due to their weaker protective capabilities. In plateau and mountainous regions, distribution lines are particularly affected by Low-amplitude Lightning (LaL) due to the shielding and attracting effects of mountains and the earth. Analyzing and assessing the overvoltage risks posed by LaL to distribution lines holds significant practical value. This paper develops a risk assessment model for distribution lines in plateau and mountainous regions, firstly, driven by actual lightning data collected by the High Precision Lightning Location System (HPLLS), found that the LaL events exhibited a notably high occurrence frequency of 46.02%. Secondly, a fractal streamlines model (FSM) for simulating the development of lightning leaders is proposed. Finally, based on the FSM, the probability and spatial distribution of LaL direct strikes are calculated, within the lightning strike range, the probability of LaL directly hitting distribution lines was close to 100%, the overvoltage caused by LaL can reach hundreds of kV, and a risk-based LaL damage assessment model is presented. This integrated methodology advances lightning risk assessment practices, providing a physics-informed foundation for enhancing the reliability of mountainous distribution networks.